The Effectiveness of PMTCT Education in Increasing Pregnant Mothers' Knowledge on HIV/AIDS Prevention for Their Babies - Wulandari, Siswi; Utomo, Bram Mustiko (CV. Get Press Indonesia, 2025)
Mother-to-child transmission (MTCT) of HIV is a pressing global health issue, particularly in regions with limited access to healthcare and education. Although advancements in prevention strategies have significantly reduced transmission rates, knowledge gaps among pregnant women often limit the effectiveness of Prevention of Mother-to-Child Transmission (PMTCT) programs. This study evaluated the impact of PMTCT education on increasing maternal knowledge and fostering adherence to HIV prevention practices.A pre-test and post-test design was implemented with 30 pregnant women attending antenatal care services in a resource-limited setting. Participants completed a knowledge assessment questionnaire before and after a culturally and linguistically tailored PMTCT education session. Data were analyzed using paired ttt-tests to evaluate knowledge improvement and logistic regression to assess changes in adherence intentions. The results showed a significant improvement in knowledge scores, increasing from 42.5% (SD = 11.7%) pre-intervention to 80.3% (SD = 8.9%) post-intervention (t(29) = 10.85, p < 0.001, Cohen's d = 2.01), and behavioral intentions to adhere to PMTCT protocols improved from 40% to 85%. Logistic regression analysis revealed a strong association between higher post-intervention knowledge scores and increased adherence intentions (OR = 5.6, 95% CI = 2.3–13.4, p < 0.001). These findings underscore the importance of integrating structured PMTCT education into antenatal care services to empower mothers, reduce MTCT rates, and enhance adherence to preventive measures. Future research should explore long-term outcomes and the inclusion of family members to amplify intervention impact.